Experimental investigation on fracture toughness of Al6061–graphite by using Circumferential Notched Tensile Specimens (Fracture and Structural Integrity, 2016)
This paper presents the experimental work carried out on the fracture behavior of aluminium 6061 (Al6061) and graphite particulate composites. The required specimens are prepared using stir casting method with graphite proportions ranging from 3 to 12 % by weight. The fracture behavior of Al6061-graphite particulate composites produced using stir casting method, was investigated by conducting experiments on Universal Testing Machine (UTM). Circumferential Notched Tensile (CNT) specimens were utilized to evaluate the fracture toughness of the composites. From the experiment the fracture toughness KIC= 15.85MPa m1/2 is obtained for Al6061-9% Graphite. Further, the experimental results revealed that, except 12% graphite, the fracture toughness of Al6061-graphite was observed to increases with an increase in weight percentage of graphite. The experimental results reinforce that Al6061-graphite particulate MMCs are suitable for automotive and aerospace applications requiring high fracture toughness apart from good wear resistance.
Keywords: Fracture Toughness; Circumferential Notched Tensile (CNT); Aluminium Graphite Particulate Composites